2022
DOI: 10.3389/fimmu.2022.839367
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Immune Responses of Serum IgG and Secretory IgA Against the Spike Protein of Endemic Coronaviruses During Severe COVID-19

Abstract: Defining immune correlates of disease severity is important to better understand the immunopathogenesis in COVID-19. Here we made use of a protein microarray platform to detect IgG- and IgA-reactive antibodies in sera and saliva respectively, and assess cross-reactivity between SARS-CoV-2 and endemic coronaviruses (eCoVs). IgG responses against the full protein of spike, but not the S1 subunit, were significantly higher in convalescent sera of patients with severe disease compared to mild disease and healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
4
11
0
Order By: Relevance
“…Similar results were found by Smit et al. ( 22 ) in an independent cohort. Conflicting results to Kaplonek et al.…”
Section: Introductionsupporting
confidence: 92%
“…Similar results were found by Smit et al. ( 22 ) in an independent cohort. Conflicting results to Kaplonek et al.…”
Section: Introductionsupporting
confidence: 92%
“…With respect to disease outcomes, McNaughton et al [21] showed that prior immunity to seasonal coronaviruses was positively associated with fatal outcomes in individuals with severe COVID-19. Similar results were found by Smit et al [22] in an independent cohort. Conflicting results to Kaplonek et al [19] were found by Garrido et al [23], who found that S2 antibody responses were associated with greater disease severity.…”
Section: Introductionsupporting
confidence: 91%
“…Accordingly, memory B cell clones directed to HCoVs boosted during severe COVID-19 indeed poorly neutralize SARS-CoV-2 8 . In our cohort, we have also reported a back boost of HCoV-related anti-spike IgG in patients with severe disease, with the strongest correlation of anti-spike IgG to SARS-CoV-2 and to the Betacoronaviruses (OC43 and HKU1) seen in severely ill patients 9 . Following up on this work, we assessed neutralizing immunity and evaluated the anti-spike IgG ratio of SARS-CoV-2 to HCoVs in the same cohort, focusing on the subgroup of deceased patients in order to identify markers of a fatal disease course.…”
Section: Introductionsupporting
confidence: 54%
“…Severe disease was divided into individuals who recovered during follow-up (termed non-fatal disease) and individuals who deceased during hospitalization or up to one week after discharge (termed fatal disease). Baseline characteristics of each of these cohort groups have previously been published 9 . We then assessed the proportion of IgG that was directed against the spike protein (S-protein) of HCoVs compared to SARS-CoV-2 using a protein array that allows for parallel and quantitatively assessment of antigen-speci c IgG 9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation